Production et reproduction sociales chez Marx - Garo, Isabelle (Bollettino Filosofico, 2025)
Today at the centre of our concerns, the question of life is present in Marx’s work. It characterises part of the natural world, but also humanity’s relationship with nature, as well as the vitality of social relations and their capacity to reproduce and transform themselves in the course of history, ensuring or threatening the perpetuation of humanity. The notion of reproduction encompasses these various dimensions. The aim is to show that, in Marx’s work, the questions of production and social reproduction are inseparable. Their linkage highlights the aggravated contradictions of the capitalist mode of production, but these contradictions also open up avenues for political intervention and social transformation, at a time when the alternatives to capitalism are themselves in deep crisis. Keywords: Communism, Crisis, Productive Forces, Social Metabolism, Social Reproduction